1996
DOI: 10.1038/ki.1996.417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute rapamycin nephrotoxicity with cyclosporine and FK506

Abstract: Acute cyclosporine (CsA) nephrotoxicity is characterized by a reduction of glomerular filtration rate (GFR), hypomagnesemia and tubular injury. The mechanisms of CsA's immunosuppressive action and presumably its nephrotoxicity are mediated through inhibition of the renal phosphatase, calcineurin. FK506 (FK), which has a different chemical structure and binding immunophilin, also inhibits calcineurin. We compared the renal effects of these drugs to those of rapamycin (RAPA), which although similar in structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(117 citation statements)
references
References 30 publications
7
108
1
1
Order By: Relevance
“…25 The major adverse effects previously reported with tacrolimus have included nephrotoxicity, neurotoxicity, hyperglycemia, and hypertension. [29][30][31][32] Other commonly reported side-effects include microangiopathic hemolytic anemias, 33 hyperkalemia, 34 hypomagnesemia, 35 and hypercholesterolemia. 36 Unlike cyclosporine, tacrolimus rarely causes gingival hyperplasia or hirsutism.…”
Section: Discussionmentioning
confidence: 99%
“…25 The major adverse effects previously reported with tacrolimus have included nephrotoxicity, neurotoxicity, hyperglycemia, and hypertension. [29][30][31][32] Other commonly reported side-effects include microangiopathic hemolytic anemias, 33 hyperkalemia, 34 hypomagnesemia, 35 and hypercholesterolemia. 36 Unlike cyclosporine, tacrolimus rarely causes gingival hyperplasia or hirsutism.…”
Section: Discussionmentioning
confidence: 99%
“…When renal blood flow and glomerular filtration rate were compared in rats treated with sirolimus (3 mg/kg/d orally), cyclosporine A (15 mg/kg/d subcutaneously), or tacrolimus (5 mg/kg/d orally), significantly better renal function was found in the sirolimus group compared with the cyclosporine A and tacrolimus groups. 74 In another study 75 of spontaneously hypertensive rats, creatinine clearance was not altered by continuous infusion of sirolimus (0.01 mg/kg), but was reduced by 20% after infusion of cyclosporine A (5 mg/kg).…”
Section: Preclinical Animal Studiesmentioning
confidence: 99%
“…Burdmann et al (27) demonstrated that there was an increase in enzymuria 14 days after CsA or FK506 administration, which did not occur with SRL. Whiting et al (28) showed that SRL and CsA together caused a significant increase in enzymuria and a reduction of GFR, both effects attributable to additive renal toxicity (29,30). Lieberthal et al (15) demonstrated that recovery of renal function was delayed in rats treated with SRL on days 3 and 4 after 40-min ischemia.…”
Section: Sham Ischemiamentioning
confidence: 99%